Management of undifferentiated adrenal gland metastases from malignant melanoma: case report - Shortreed, Hannah; Burute, Nishigandha; Aseyev, Olexiy (Frontiers in Oncology, 2024)
Adrenal gland metastases from malignant melanoma are a common but poorly characterised condition. Their lack of consistent clinical features and poor response to immune checkpoint inhibitors pose a significant diagnostic and therapeutic challenge to practitioners. This case report describes a 78-year-old male with no prior history of melanoma presenting with nonspecific abdominal symptoms and unintentional weight loss who was found to have undifferentiated bilateral adrenal gland metastases from malignant melanoma. Despite ongoing investigations, the primary site of the adrenal gland metastases remained unknown, prompting the consideration of primary adrenal melanoma as a diagnosis. The patient underwent four cycles of treatment with immune checkpoint inhibitors, nivolumab and ipilimumab, followed by maintenance therapy and subsequent adrenal metastasectomy. Despite therapeutic efforts, the patient's tumour was resistant to treatment and became undifferentiated. The patient continued with palliative care until his death, more than three years after the onset of symptoms. The clinical features, pathophysiology, diagnosis, treatment, and prognosis of this patient's disease are discussed in detail to help inform the management of similar cases.